Analysis of the Noise Characteristic of Automotive Engine Timing Chain System - Xu Shuxin; Ye Bin; Fan Chengyan; Meng Fanzhong (Jixie chuandong)
The noise of automobile engine valve timing mechanism is one of the main sources of engine mechanical noise,which is directly related to the power performance of the engine. With the cylinder head anti drag system test bench,by using orthogonal design method,the noise characteristics of the engine in different lubricating oil temperature,oil pressure,rotational speed of the crankshaft are tested. A new means and methods to obtain the transmission noise characteristics of the timing is proposed. In the process of test,the emphasis should be put on the mechanical noise of the timing drive chain and the camshaft. Compared to other forms of chain transmission noise test,it is more close to the actual operating conditions of timing chain system. The research shows that it can effectively reduce the overall noise level of the timing drive system by changing tensioner hydraulic and lubricating oil temperature,which is of great reference value to the research and development of timing drive system.